The conservation significance of natural hybridisation in Mediterranean plants: from a case study on Cyclamen (Primulaceae) to a general perspective. (28th September 2017) - Thompson, J. D.; Gauthier, P.; Papuga, G.; Pons, V.; Debussche, M.; Farris, E.
Abstract: Hybridisation plays a prominent role in plant evolution due to its influence on genetic diversity, fitness and adaptive potential. We identify a case of on‐going hybrid evolution of floral phenotypes in disjunct populations of Cyclamen balearicum and C. repandum subsp. repandum on Corsica and Sardinia. Hybrid populations on the two islands contain similar patterns of variation in flower colour and size but are probably at different stages in the evolutionary process of hybridisation, and differences in the frequency of floral types and flower size suggest hybrid vigour that may contribute to the dynamics and maintenance of hybrid forms. In a review of cases of hybridisation in Mediterranean plants we found an equivalent number of cases for the contemporary occurrence of mixed hybrid populations, as there are cases of homoploid hybrid species differentiation. We argue for the development of a conservation strategy for Mediterranean plants that integrates the need to protect not just pure endemic species (some of hybrid origin) but also mixed populations where adaptive variation and new species are evolving due to contemporary hybridisation.